Dinamika Kuasa Lokal dan Politik Anggaran : Ekspose Korupsi Struktural dalam Sistem Pengadaan di Bima dan Dompu - Firmansyah Firmansyah; Haeril Haeril; Akhyar Akhyar; Arief Hidayatullah (Badan Penerbit STIEPARI Press, 2025)
This study aims to critically unveil the embedded structure of systemic corruption within the public procurement system across Bima City, Bima Regency, and Dompu Regency, which reflects the pathological convergence of state capture, neo-patrimonialism, and crony capitalism. Utilizing a critical qualitative method with an intrinsic case study design, the research applies Foucauldian governmentality, institutional corruption theory, and Baudrillard’s simulacra to deconstruct how procurement mechanisms are no longer administrative tools but instead function as instruments of predatory power consolidation. The data gathered through elite interviews, document analysis of court verdicts, audit reports, and participatory observation were analyzed using critical discourse analysis within an abductive logic framework. The findings reveal that procurement processes in the three regions are systematically hijacked by political elites through premeditated collusion, falsified documents, and bureaucratic manipulation, all legitimized via simulated legality. In Bima City, former mayor Lutfi orchestrated a vertical network of rent-seeking embedded in the bureaucracy. Bima Regency institutionalized kleptocracy via project cartels, while Dompu demonstrates the most severe decay, where law enforcement, bureaucratic apparatuses, and political elites form a mutual protection pact. The study concludes that procurement corruption is not a deviation but an institutionalized governance model, undermining democratic accountability and transforming procurement into a mechanism for redistributing economic and political power among oligarchic networks.